Collection management for youth: responding to the needs of learners - Hughes-Hassell, Sandra; Mancall, Jacqueline C. (American Library Association, 2005)
It's no longer about just about having the "best" collection. As education shifts to a learner-centered environment, collection development must address the dynamic interplay between all stakeholders in the wider school community. Based on the latest educational theory and research, Hughes-Hassell and Mancall recommend a plan to operate school media centers in the midst of radical flux, while meeting students' information needs in a holistic context.